2009
DOI: 10.2306/scienceasia1513-1874.2009.35.137
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Herpes simplex virus type 1 (HSV-1) causes a variety of infections in humans and can be found in many countries worldwide. Although the antiherpes drug, acyclovir, has been used very successfully, an acyclovir-resistant strain of HSV has recently been found in patients and drug toxicity has been reported with increasing use of it. As a potential alternative, it has been found that both a water soluble and a lipid extract of the microalga Spirulina platensis exhibit antiviral activity (HSV-1) in Vero cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Marine phospholipids offer higher bioaccessibility and bioavailability of omega-3 lipids than triglycerides, and several phospholipids have also been reported with beneficial health effects in the prevention of several chronic diseases, such as cardiovascular diseases [8]. Marine glycolipids from the genus Nannochloropsis are also rich in omega-3 lipids and have been associated with anti-tumoral [9,10], antiviral [11,12], antibacterial [13], and anti-inflammatory [14][15][16][17] activities. They have also been described with several beneficial effects on senescence, cognitive functions, and inflammatory diseases, as well as on plasma and hepatic lipid metabolism [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Marine phospholipids offer higher bioaccessibility and bioavailability of omega-3 lipids than triglycerides, and several phospholipids have also been reported with beneficial health effects in the prevention of several chronic diseases, such as cardiovascular diseases [8]. Marine glycolipids from the genus Nannochloropsis are also rich in omega-3 lipids and have been associated with anti-tumoral [9,10], antiviral [11,12], antibacterial [13], and anti-inflammatory [14][15][16][17] activities. They have also been described with several beneficial effects on senescence, cognitive functions, and inflammatory diseases, as well as on plasma and hepatic lipid metabolism [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous report of Cepoi et al indicated that, Spirulina Platensis is an ideal selection for NPs bio-fabrication because the cells have many bioactive reducing compounds (Cepoi et al, 2015). Arthrospira sp extracts have been reported to exhibit diverse activity as anticoagulant (Majdoub et al, 2009) and antiviral effects (Chirasuwan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfolipid compounds in spirulina have an important role in the human body in maintaining the body's resistance. Sulfoquinovosyl diacylglycerol (SQDG) compound is one of the sulfolipids extracted from Spirulina platensis, and it can be an inhibitor of herpes simplex virus type 1 (HSV-1) which can damage the human immune system [3]. High nutrition and bioactive compounds in Spirulina platensis can be a solution to the problem of malnutrition in various countries, such as vitamin A deficiency and hunger edema.…”
Section: Introductionmentioning
confidence: 99%